2005
DOI: 10.1295/polymj.37.913
|View full text |Cite
|
Sign up to set email alerts
|

Wormlike Micelles of Polyoxyethylene Dodecyl C12Ej and Heptaoxyethylene Alkyl CiE7 Ethers. Hydrophobic and Hydrophilic Chain Length Dependence of the Micellar Characteristics

Abstract: ABSTRACT:The micelles formed with pentaoxyethylene C 12 E 5 and heptaoxyethylene C 12 E 7 dodecyl ethers and heptaoxyethylene tetradecyl ether C 14 E 7 in dilute aqueous solutions were characterized by static (SLS) and dynamic light scattering (DLS) experiments at several temperatures T below the critical points. The SLS results were successfully analyzed by using a thermodynamic theory formulated with wormlike spherocylinder model for SLS of micelle solutions, thereby yielding the molar mass M w of the micell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
49
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(62 citation statements)
references
References 33 publications
13
49
0
Order By: Relevance
“…The weight average molecular weight of the C 12 E 5 + n-dodecanol mixture calculated with a given w d was used as the surfactant molecular weight M 0 required in the theoretical analysis. 1=2 in the range of c examined, as in the case of the previous findings for the micelles formed with single surfactant of various type, [1][2][3][4][5]7 for those formed with binary C i E j mixtures, 8,9 and the C 10 E 5 micelles containing n-dodecanol. 18 These results are in good correspondence with simple theoretical predictions derived from the thermodynamic treatments of multiple equilibria among micelles of various aggregation numbers.…”
Section: Analysis Of Sls Datasupporting
confidence: 73%
See 2 more Smart Citations
“…The weight average molecular weight of the C 12 E 5 + n-dodecanol mixture calculated with a given w d was used as the surfactant molecular weight M 0 required in the theoretical analysis. 1=2 in the range of c examined, as in the case of the previous findings for the micelles formed with single surfactant of various type, [1][2][3][4][5]7 for those formed with binary C i E j mixtures, 8,9 and the C 10 E 5 micelles containing n-dodecanol. 18 These results are in good correspondence with simple theoretical predictions derived from the thermodynamic treatments of multiple equilibria among micelles of various aggregation numbers.…”
Section: Analysis Of Sls Datasupporting
confidence: 73%
“…As in the previous studies, [1][2][3][4][5][7][8][9]18 the SLS results Kc=ÁR 0 successfully analyzed with the aid of the theory 10 for light scattering of micelle solutions formulated with wormlike spherocylinder model, to yield the molar mass M w ðcÞ as a function of c along with the cross-sectional diameter d of the micelle. It has been found that the mean-square radius of gyration hS 2 i as a function of M w is well described by the Benoit-Doty equation 12 for the wormlike chain model.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] In the work, we have been able to determine the concentration-dependent characteristics of the micelles by separating contributions of the intermicellar thermodynamic and hydrodynamic interactions to the SLS and DLS results with the aid of the corresponding theories. We have determined the weight-average molar mass M w of the micelles as a function of surfactant mass concentration c along with the cross-sectional diameter d from the SLS data by using a molecular thermodynamic theory 21,38 formulated with the wormlike spherocylinder model.…”
mentioning
confidence: 99%
“…We have determined the weight-average molar mass M w of the micelles as a function of surfactant mass concentration c along with the cross-sectional diameter d from the SLS data by using a molecular thermodynamic theory 21,38 formulated with the wormlike spherocylinder model. It has then found that the molar mass M w dependence of mean-square radius of gyration hS 2 i, hydrodynamic radius R H , and intrinsic viscosity [] for the micelles of pure C i E j with various i and j [22][23][24][25][26][27][28] and their binary mixtures 29,30 is quantitatively represented by the chain statistical 39 and hydrodynamic theories [40][41][42][43] based on the wormlike chain and spherocylinder models, respectively. In particular, it has been demonstrated that the fuzzy cylinder theory [44][45][46][47] is favorably applied to analyze the apparent hydrodynamic radius R H,app , which is directly obtained from DLS experiment, as a function of the micelle concentration, thereby yielding the concentration-dependent micellar growth by separating contributions of the enhancement of hydrodynamic interactions among micelles with increasing concentration.…”
mentioning
confidence: 99%